Corynebacterium striatum: an emerging respiratory pathogen - Malini Shariff; Aditi Aditi; Kiran Beri (Journal of Infection in Developing Countries)
Introduction: Corynebacterium spp. are primarily considered normal flora and dismissed when isolated from clinical specimens. In recent years, Corynebacterium striatum has emerged as a multi-drug resistant human pathogen which can cause nosocomial outbreaks. The organism has infrequently been noted to cause respiratory infections. A retrospective study was conducted to identify the clinical and microbiological features of respiratory infection by Corynebacterium striatum.